Contralateral Prophylactic Mastectomy in the American College of Radiology Imaging Network 6667 Trial: Effect of Breast MR Imaging Assessments and Patient Characteristics - Rahbar, Habib (Radiology, 2014)
PURPOSE: To assess which patient and magnetic resonance (MR) imaging factors are associated with the likelihood of contralateral prophylactic mastectomy (CPM) in patients with newly diagnosed breast cancer. MATERIALS AND METHODS: The American College of Radiology Imaging Network 6667 trial was compliant with HIPAA; institutional review board approval was obtained at each site. All patients provided written informed consent. This study was a retrospective review of data from 934 women enrolled in the trial who did not have a known contralateral breast cancer at the time of surgical planning. The authors assessed age, menopausal status, index breast cancer histologic results, contralateral breast histologic results, breast density, family history, race and/or ethnicity, MR imaging Breast Imaging Reporting and Data System (BI-RADS) assessment, and number of MR imaging lesions for association with CPM by using the Fisher exact test, exact χ(2) test, and multivariate logistic regression analyses. RESULTS: Eighty-six of the 934 (9.2%) women underwent CPM and were more likely to be younger (mean age, 48 years [range, 27–78 years] vs mean age, 54 years [range, 25–86 years]; P < .0001), be premenopausal (55 of 86 [64%] vs 349 of 845 [41%], P < .0001), have ductal carcinoma in situ (DCIS) in the index breast (31% [27 of 86] vs 19% [164 of 848], P = .02), have greater breast density (71 of 86 [83%] vs 572 of 848 [68%], P = .004), and have a family history of breast cancer (44 of 86 [30%] vs 150 of 488 [18%], P = .01) than those who did not undergo CPM. Distributions of race and/or ethnicity, contralateral lesion pathologic results, and number of MR imaging lesions were similar in both groups. With multivariate modeling, younger age, greater breast density, DCIS index cancer, and family history remained significant, whereas menopausal status did not. Positive MR imaging assessments were not significantly more frequent in the CPM group than in the group of women who did not undergo CPM (14 of 86 [16.3%] vs 113 of 848 [13.3%], P = .43). CONCLUSION: In patients with newly diagnosed breast cancer who underwent breast MR imaging at which a contralateral breast cancer was not identified, patient factors and not breast MR imaging BI-RADS scores were chief determinants in decisions regarding CPM. © RSNA, 2014 Online supplemental material is available for this article.